Foot care behaviors among adults with type 2 diabetes. Issue 6 (December 2016) - D'Souza, Melba Sheila; Ruppert, Susan D.; Parahoo, Kader; Karkada, Subrahmanya Nairy; Amirtharaj, Anandhi; Jacob, Devakirubai; Balachandran, Shreedevi; Al Salmi, Nasser Majid Dhabi
Highlights: Adults with foot problems and ulcers require foot care prevention and management. Socio-economic and clinical factors were correlated with foot care problems. Target high-risk adults with foot problems through knowledge, skills and education. Abstract: Aim: The aim of the study was to determine factors influencing foot care behaviors among adults with type 2 diabetes. Methods: A correlational descriptive study was conducted with a random sample of 160 adults with type 2 diabetes from the public hospital between April and July 2014. Results: Just over 15% of the sample had a history of foot ulcers and almost 42% had numbness/tingling and pain in their feet. Positive foot care behaviors were correlated with higher income, higher educational attainment, lower body weight, positive attitude and higher awareness of diabetes and its management. Conclusion: Targeting type 2 diabetes people with low level of education, low income and overweight may help to enhance their foot care and reduce foot complications in similar populations, Implications. Those most at risk of foot problems should be targeted for education to increase their awareness of ways to prevent and to manage foot problems.